BULLYING VERBAL: ANALISIS PREDIKTOR MOTIVASI BELAJAR SISWA SEKOLAH DASAR - Fajar Najua Syalsabila; Yustizar; Febriyantika Wulandari (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Verbal bullying is a form of bullying that frequently occurs in elementary school settings and has the potential to affect students’ psychological well-being, including their motivation to learn. However, there has been little research specifically examining verbal bullying as a predictor of elementary school students’ motivation to learn. This study aims to analyze whether verbal bullying is a significant predictor of elementary school students’ motivation to learn. The study employed a quantitative approach with an ex post facto design. The study population consisted of all fifth-grade students at MIN 1 Langsa for the 2026 academic year, totaling 144 students. The sample comprised 31 students from Class 5E, selected using cluster random sampling. Data were collected through a questionnaire that had passed validity and reliability tests, then analyzed using simple linear regression. The results showed that verbal bullying was not a significant predictor of students’ learning motivation (β = -0.103; t = -0.559; p = 0.581). The coefficient of determination (R² = 0.011) indicates that verbal bullying contributes only 1.1% to the variation in learning motivation, while 98.9% is influenced by other factors outside the scope of this study. Thus, verbal bullying is not a significant predictor of learning motivation among elementary school students.